ANALISIS EFISIENSI PASAR MODAL INDONESIA BENTUK LEMAH PERIODE AGUSTUS 2009 SAMPAI JULI 2012 - B11108036, Dian Kristiani (Jurnal Manajemen Update, 2013)
An efficient market is very important in helping investors make investment decisions. Market efficiency can be classified into three categories: weak, semi-strong and strong. Capital market efficiency is categorized into weak-form if the prices of securities is reflecting the information from the past. The purpose of this research is to analyze whether Indonesias capital market is following random walk pattern or not. This research is using samples taken from the Composite Stock Price Index (CCI) from August 2009 to July 2012. CCI was chosen as research material because its role as an indicator of price movement on the stock exchange. Regression test and Run test is used to determine the randomness of stock prices. The results of the regression tests provide not correlation between the stock price from the past with the current share prices. The results of the run test indicated that the stock price is a random pattern. I can be concluded that the Indonesian stock market during the period of August 2009 to July 2012 is efficient in the weak form. Keywords: Efficient Capital Markets, Capital Market Efficiency Weak-form, Regression Test, Run Test